A framework for the evaluation of the structural safety of existing concrete gravity dams - Dankers, Clyde Lleland (Department of Civil Engineering, 2020)
Addressing the aging and deterioration of dams is a relatively new challenge in the dam engineering field in South Africa. The average life expectancy of a dam is approximately 50 years, but they can normally be used for much longer periods than this. Maintenance and rehabilitation are vital to ensure that they achieve their design service lives and for the extension of their service lives. The rehabilitation of dams to extend their service lives and/or to ensure that they comply with modern stability criteria can be an extremely lengthy and costly exercise. It would therefore be valuable to do some research into the process of evaluating the structural safety of dams. The focus of this research study is specifically on the evaluation of the structural safety of large concrete gravity dams. The purpose of the research is to investigate the most commonly used and accepted methods to evaluate the structural safety of concrete gravity dams and develop a framework that can be used for the evaluation of the structural safety of concrete gravity dams. For the purpose of this research study, an existing large concrete gravity dam was evaluated as a case study. The dam is approximately 93 years old and provides water to the nearby local municipality for domestic purposes. According to the first and second Dam Safety Evaluation (DSE) reports the dam does not comply with modern stability criteria for concrete gravity dams. The findings of these dam safety evaluation reports led to the dam being labelled as essentially “unsafe” in the case of the occurrence of a large flood. Typically, this would mean that the dam must be rehabilitated to improve its safety. However, some engineers believe that this is not the case and that major rehabilitation is not necessary. In this research study a framework for the evaluation of the structural safety of existing concrete gravity dams was developed based on lessons learnt from the literature review and the case study. This recommended framework can be useful as a guide for future safety evaluations of existing concrete gravity dams. The potential benefits of using this recommended framework includes avoiding unnecessary rehabilitation work, as well as significant time and cost savings.